2007
DOI: 10.1016/j.febslet.2007.01.064
|View full text |Cite
|
Sign up to set email alerts
|

Ether stress‐induced Alzheimer‐like tau phosphorylation in the normal mouse brain

Abstract: Tau is reversibly hyperphosphorylated in the mouse brain by starvation or cold water swimming. Here, we report tau phosphorylation in the hippocampus of normal mouse after ether anesthesia, known to trigger typical stress reactions. Robust phosphorylation of tau was observed immediately and 10 min after ether vapor exposure at Ser202/Thr205 and Thr231/Ser235, sites typically phosphorylated in Alzheimer brains. The phosphorylation levels returned to baseline by 1 h. The most conspicuous and consistent change in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 49 publications
4
39
0
Order By: Relevance
“…Recently, it became known that different forms of acute stress can induce the transient phosphorylation of tau protein (Feng et al 2005;Ikeda et al 2007;Rissman 2009;Sotiropoulos et al 2011). Our data presented above are in agreement with results published by these authors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Recently, it became known that different forms of acute stress can induce the transient phosphorylation of tau protein (Feng et al 2005;Ikeda et al 2007;Rissman 2009;Sotiropoulos et al 2011). Our data presented above are in agreement with results published by these authors.…”
Section: Discussionsupporting
confidence: 93%
“…Most of the papers dealing with the effect of stress on tau protein phosphorylation published to date are focused on the analysis of the prefrontal cortex and hippocampus (Feng et al 2005;Rissman et al 2007;Ikeda et al 2007). Little is known about the pathological tau phosphorylation in other brain areas.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in tau phosphorylation level at Ser202/Thr205 (AT8 site) was observed in the hippocampus of Tg2576 mice treated with saline. Phosphotau is an integral component of the NFT deposits that disrupt neuronal function, and it is possible that dysregulation of tau phosphorylation in the hippocampus can be translated into a memory impairment in the development of synaptic dysfunction such as AD (Arendt et al, 2003;Ikeda et al, 2007). Here, we found that phospho-tau levels did not differ between the transgenic 4-PBA-treated mice and the non-transgenic mice.…”
Section: Discussionmentioning
confidence: 53%
“…In contrast to our previous study where a high CORT level was found upon chronic isolation [31] , in this study we found low levels of CORT in the blood serum of chronically stressed animals relative to the control. This discrepancy is likely due to the exclusion of ether anesthesia prior to sacrifice [32][33][34] . The current finding of low CORT in isolated animals is similar to the results of other authors showing HPA axis hypoactivity in stress conditions caused by isolation on either young animals or animals subjected to social isolation for shorter periods of time [35,36] .…”
Section: Discussionmentioning
confidence: 99%